2021
DOI: 10.1038/s41598-021-88610-z
|View full text |Cite
|
Sign up to set email alerts
|

PKR activity modulation by phosphomimetic mutations of serine residues located three aminoacids upstream of double-stranded RNA binding motifs

Abstract: Eukaryotic translation initiation factor 2 alpha kinase 2 (EIF2AK2), better known as PKR, plays a key role in the response to viral infections and cellular homeostasis by regulating mRNA translation. Upon binding dsRNA, PKR is activated through homodimerization and subsequent autophosphorylation on residues Thr446 and Thr451. In this study, we identified a novel PKR phosphorylation site, Ser6, located 3 amino acids upstream of the first double-stranded RNA binding motif (DRBM1). Another Ser residue occurs in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
(80 reference statements)
1
13
0
Order By: Relevance
“…Instead, it interferes with dsRNA association to PKR by binding and hijacking host kinases, RSKs 41• , 42•• . How this suppresses PKR activation is unknown, but this observation adds to the notion that regulation of PKR activation is more complex than generally assumed, as also recently proposed by others 43 , 44 . Additionally, it has been suggested that L interferes with the interaction between eIF4G and G3BP to suppress SG formation [27•] .…”
Section: Picornavirus Isr Antagonistssupporting
confidence: 55%
“…Instead, it interferes with dsRNA association to PKR by binding and hijacking host kinases, RSKs 41• , 42•• . How this suppresses PKR activation is unknown, but this observation adds to the notion that regulation of PKR activation is more complex than generally assumed, as also recently proposed by others 43 , 44 . Additionally, it has been suggested that L interferes with the interaction between eIF4G and G3BP to suppress SG formation [27•] .…”
Section: Picornavirus Isr Antagonistssupporting
confidence: 55%
“…Other lentiviral vectors used for protein expression were derived from pCCLsin.PPT.hPGK.GFP.pre. 47 - TM945 is a Prom CMV -MCS-IRES-mCherry construct 48 - TM952 is a Prom CMV -MCS-IRES-neo construct 49 - BLP10 is a TM952 derivative coding for BioID2-HA-linker(3xGGGS)-MuRSK2. This construct expresses murine RSK2, which differs from human RSK2 by a single amino acid. - BLP20 is a TM952 derivative coding for As1-RSK2 (hu-RSK2 with Analog-sensitive kinase 1 (As1) mutation (Leu 147 → Gly). - BLP21 is a TM952 derivative coding for As2-RSK2 (hu-RSK2 with Analog-sensitive kinase 2 (As2) mutation (Leu 147 → Ala). - CL13 is a TM945 derivative expressing the 10 C-terminal aminoacids of L followed by the entire capsid precursor of virus DA1. - TM1116, TM1117, TM1118 and TM1119 are TM952 derivatives carrying the sequences coding for 3xHA-Human RSK1, RSK2, RSK3 and RSK4 respectively 1 .…”
Section: Methodsmentioning
confidence: 99%
“…-pLVX-EF1alpha-2xGFP:NES-IRES-2xRFP:NLS was a gift from Fred Gage (Addgene plasmid # 71396) (Mertens et al, 2015) Other lentiviral vectors used for protein expression were derived from pCCLsin.PPT.hPGK.GFP.pre. (Follenzi et al, 2000) -TM945 is a PromCMV-MCS-IRES-mCherry construct (Hermant et al, 2013) -TM952 is a PromCMV-MCS-IRES-neo construct (Cesaro et al, 2021) -BLP10 is a TM952 derivative coding for BioID2-HA-linker(3xGGGS)-MuRSK2. Note that this construct expresses murine RSK2, which differs from human RSK2 by a single amino acid.…”
Section: Lentiviral Vectors and Cell Transductionmentioning
confidence: 99%
“…Moreover, PKR plays a key role in the viral infection response and intracellular homeostasis by regulating the translation of mRNAs. After dsRNA binds to PKR, PKR is activated through homozygous dimerization and autophosphorylation of Thr446 and Thr451 residues 32 . Upon inflammation or virus infection, circRNAs are globally degraded by activated RNase L, releasing PKR for its aberrant activation, as seen in SLE patients with reduced degradation of circRNAs leading to increased aberrant activation of PKR (Fig.…”
Section: Main Textmentioning
confidence: 99%